Fluid baths to ensure the stability of wellbores - Yurych, L. R.; Yurych, А. R.; Pytak, D. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2026)
The causes of wellbore wall collapses and caving during the drilling of oil and gas wells have been investigated. The main geomechanical and physicochemical processes leading to a decrease in rock stability were examined, in particular, a reduction in lateral pressure, the penetration of drilling fluid filtrate, and hydration processes. The influence of crystalline and osmotic swelling mechanisms on the structural and mechanical properties of rocks was established. Fluid baths for ensuring wellbore stability are analyzed. The composition, mechanisms of action, as well as the advantages and disadvantages of fluid baths are examined. It is established that the effectiveness of fluid baths is determined by their ability to reduce the intensity of clay hydration. The analysis concluded that a rational selection of the fluid bath type, taking into account the lithological characteristics of the rocks and drilling conditions, allows for increased wellbore stability, a reduction in the number of complications, and improved drilling efficiency